Comparative analysis of briquettes obtained from biomass and charcoal. (2021) - Ajith Kumar, J.; Vinoth Kumar, K.; Petchimuthu, M.; Iyahraja, S.; Vignesh Kumar, D.
Abstract: It is well known that there is a need for large amount of energy from alternate fuels due to the depletion of fossil fuels and increased energy demand. This paper analyses the important properties of biomass, charcoal with and without binder as alternate fuels. Also, the effect of solid and hollow briquettes on ash, moisture contents and volatile matter of the briquettes are studied. The briquettes are made from wood waste and charcoal. Starch has been used as binder with charcoal. The calorific value, moisture content, ash content and volatile matter were estimated. The investigation shows that the pure charcoal possesses higher calorific value than that with binder and biomass. However the addition of binder can reduce ash content, moisture content and volatile matter which may lead to the benefits of reduced corrosion effect.